A modified Vogel's medium for crossings, mating-type tests and the isolation of female-sterile mutants of Neurospora crassa. - V. E.A. Russo; T. Sommer; J. A.A. Chambers (Fungal Genetics Reports, 1985)
A modified Vogel's medium for crossing, mating-type tests and the isolation of female-sterile mutants of Neurospora crassa.